Embryo quality in intracytoplasmic sperm injection: A quasi experimental design in Pakistan - Rehman, Rehana; Irfan, Tooba; Jawed, Shireen; Hussain, Mehwish; Ali, Rabiya (Journal of the Pakistan Medical Association, 2018)
To assess the role of good-quality embryos in acquiring pregnancy after intracytoplasmic sperm injection and to predict factors required for development of embryos. The quasi-experimental study was conducted from June 2010 to August 2012 at Islamabad Clinic Serving Infertile Couples and comprised infertile females who received long-term gonadotropin agonist protocol for intracytoplasmic sperm injection. Basal estradiol and antral follicle count was measured at baseline, while estradiol, progesterone and interleukin levels with pre-ovulatory follicle count were evaluated on the ovulation induction day. Follicular output rate was measured as ratio of pre-ovulatory follicle count to antral follicle count. The quality of embryos was graded as good, fair and poor on the third day after the injection. Linear regression was employed to determine unadjusted and adjusted estimate of effect of different factors on good-quality embryo. There were282 subjects with a mean age of 32.1±4.7 years (range: 23-41 years). There was an inverse correlation of body mass index with good-quality embryo (r=-0.131). In adjusted analyses, basal estradiol and progesterone on the ovulation induction day showed negative effect (95% confidence interval: -1.42 - -1.01), while estradiol and interleukin measured positive effect on quality of embryo (p<0.05). Follicular output rate was highly positively correlated with good quality embryo (p<0.05).. Females with low body mass index produced good-quality embryos. A high follicular output rate with production of estradiol and interleukin complemented good-quality embryos.